Effects of radiation mitigating amino acid mixture on mice of different sexes - Xiao, Mang; Hull, Lisa; Zizzo, Alex; Lin, Bin; Zhai, Min; Wang, Li; Cui, Wanchang (Frontiers in Public Health, 2024)
To date, few FDA-approved medical countermeasures are available for addressing hematopoietic acute radiation syndrome (H-ARS). In this study, we present our latest research findings focusing on the evaluation of a novel radiation mitigator known as the mitigating amino acid mixture (MAAM). MAAM is composed of five amino acids as the recently reported amino acid-based oral rehydration solution for mitigating gastrointestinal (GI)-ARS. CD2F1 male and female mice were exposed to 60Co-γ total body irradiation (TBI) at 9.0 or 9.5 Gy. Following irradiation, mice were orally administered with MAAM or a saline vehicle control once daily for a duration of 14 days, commencing 24 h after TBI. Mouse survival and body weight change were monitored for 30 days after irradiation. Complete blood counts (CBCs), bone marrow (BM) stem and progenitor cell survival (clonogenicity), and a serum cytokine antibody array were analyzed using samples from day 30 surviving mice. Our data revealed that MAAM treatment significantly enhanced survival rates in irradiated male CD2F1 mice, and the survival rate increased from 25% in the vehicle control group to 60% in the MAAM-treated group (p < 0.05) after 9.0 Gy TBI. The number of BM colonies significantly increased from 41.8 ± 6.4 /104 cells (in the vehicle group) to 78.5 ± 17.0 /104 cells (in the MAAM group) following 9.0 Gy TBI. Furthermore, MAAM treatment led to a decrease in the levels of six cytokines/proteins [cluster of differentiation 40 (CD40), interleukin (IL)-17A, C–X–C motif chemokine 10 (CXCL10/CRG-2), cutaneous T cell-attracting chemokine (CTACK), macrophage inflammatory protein (MIP)-3β, and IL-1β] and an increase in the levels of five other cytokines/proteins [IL-3Rβ, IL-5, leptin, IL-6, and stem cell factor (SCF)] in mouse serum compared to the vehicle group after 9.0 Gy TBI. However, similar alleviating effects of MAAM were not observed in the irradiated CD2F1 female mice. The serum cytokine profile in the irradiated female mice was different compared to the irradiated male mice. In summary, our data suggest that the beneficial effects of the mitigative amino acid combination treatment after radiation exposure may depend on sex.